DOP52 Safety of Inflammatory Bowel Disease drugs during pregnancy and breastfeeding: Mothers and babies' outcomes (DUMBO registry). (27th May 2021) - Chaparro, M; García Donday, M; Calviño Suarez, C; Rubio, S; Figueira, M; Pérez Martínez, I; Leo Carnerero, E; Rodríguez Lago, I; Ruiz Cerulla, A; Aguas, M; López Serrano, P; Ramírez de la Piscina Urraca, P; et al.
Abstract: Background: Prospective registries are necessary to evaluate the safety of inflammatory bowel disease (IBD) treatment during pregnancy and in children in the long term. Aims: The overall aim of DUMBO registry is to know the risk of serious adverse events (SAEs) during pregnancy and in children up to 4 years of age exposed during pregnancy to drugs for IBD (mainly focused on biologics), compared to unexposed children. In this analysis we aim to evaluate the risk of SAEs during pregnancy and the predictive factors of it (mainly focused on IBD drugs). Methods: Prospective, observational and multicentre registry, which enrols pregnant women with IBD (Crohn's disease, ulcerative colitis, IBD-unclassified) over 5 years in 70 centres in Spain. The registry was kicked off in September 2019. SAE was defined based on "Clinical Safety Data Management: Definitions and Standards for Expedited Reporting by European Medicines Agency". Study protocol is summarized in figure 1. Results: 433 women have been included so far; 241 got pregnant at least 9 months before this interim analysis (table 1). Mean age was 34 years, and 17% of women had active disease at any time during pregnancy. 23% of pregnancies were exposed to immumodulators (thiopurines), 25% to biologics and 10% to combo therapy (biologics and immunomodulators). 85 pregnancies (35%) were exposed to biologics (60 anti-TNF, 17 ustekinumab, and 8 vedolizumab) either in combo or in monotherapy. There were 237 newborns (227 singleton and 5 pair of twins), 9 miscarriages and 1 abortion. 72% of patients had vaginal delivery and 28% C-sections (18% due to perianal CD or active disease). A total of 59 pregnancies (24.5%) reported at least one SAE: 32% in exposed to biologics and 20.5% in non-exposed group (p>0.05) (figure 2). Four out of 17 pregnancies exposed to ustekinumab and 3 out of 8 exposed to vedolizumab had SAEs (non-related with the drug). In the multivariate analysis, adjusted by disease activity, in comparison with no immunosuppressive treatment, neither immunosuppressants [Odds ratio (OR)=1.1, 95% confidence interval (CI)=0.3–4.3] nor biologics in monotherapy or in combo (OR=0.8; 95%CI=0.2–3) were associated with higher risk of SAEs. 40 patients (17%) were hospitalised due to complications during pregnancy or delivery (figure 3). Two patients underwent surgery during pregnancy due to IBD complications Conclusion: IBD treatment (either immunomodulators or biologics) does not increase the risk of SAEs during pregnancy. Nevertheless, one-quarter of IBD women suffer SAEs during pregnancy and about 20% need hospitalisation, which should be taken into account when managing IBD during pregnancy.